Overview of lr-kallisto pseudoalignment algorithm. - Rebekah K. Loving (16988427) (2025)
The input consists of a reference transcriptome and reads from a long read RNA sequencing experiment. (A) An example of two reads (blue and green with unmapping regions (black) and erroneously mapped regions (purple)) and three (pink, blue, and green) overlapping transcripts. (B) An index is constructed by creating the transcriptome de Bruijn Graph (T-DBG) where nodes are k-mers, each transcript corresponds to a colored path as shown and the path cover of the transcriptome induces transcript compatibility class (TCC) for each k-mer. (C) Conceptually, the k-mers of a read are hashed (black nodes) to find the TCC of a read. (D) The TCC of the read is determined by taking the intersection of the transcript compatibility classes of its constituent k-mers, if it exists; otherwise, the mode of the TCCs of the k-mers of the read is taken. Created with https://BioRender.com